Transformational Leadership and Competency Effects on Sustainable Performance: The Mediating Role of Innovative Behavior - Danang Suwandono; Lenny Christina Nawangsari (ARE Publisher, 2026)
This study examines the influence of competency and transformational leadership on sustainable employee performance through innovative behavior at Politeknik Pelayaran Banten. The research addresses the challenge of sustaining employee performance amid dynamic organizational changes by emphasizing long-term capability development rather than short-term productivity. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected through questionnaires distributed to employees, measuring four constructs: competency, transformational leadership, innovative behavior, and sustainable employee performance. All indicators demonstrated strong validity and reliability (outer loadings > 0.70). The findings reveal that competency and transformational leadership positively and significantly affect sustainable employee performance, both directly and indirectly through innovative behavior. Transformational leadership shows a stronger influence in stimulating innovation and sustaining performance. Innovative behavior significantly mediates the relationship between competency, leadership, and sustainable performance. The study concludes that developing employee competencies and strengthening transformational leadership are strategic drivers for fostering innovation and ensuring long-term sustainable performance. Organizations are therefore encouraged to implement competency-based human resource development and promote visionary leadership to enhance organizational sustainability.